The Influence Of The Application Of Cooperative Learning Model Type Student Team Achievement Division (Stad) On The Science Learning Outcomes Of Grade V Students At Sdn Panaikang 1, Panakukang Subdistrict, Makassar City - Sopi Paris; Salwah Salwah; Khaerun Nisa’a Tayibu (Universitas Cokroaminoto Palopo, 2026)
This study is an experimental research project aimed at determining whether the implementation of the STAD-type cooperative learning model affects the science learning outcomes of Grade V students at SDN Panaikang 1, Panakukang District, Makassar City. The independent variable in this study is the implementation of the STAD-type cooperative learning model, while the dependent variable is the students' science learning outcomes regarding the water cycle topic. The population consisted of all Grade V students at SDN Panaikang 1, Panakukang District, Makassar City, while the sample comprised Grade V.a students (35 students). A non-probability sampling technique—specifically purposive sampling—was used to select the sample; Class V.a (35 students) was designated as the experimental class, and Class V.b (31 students) as the control class. Data collection techniques included observation, testing, and documentation. Data analysis involved both descriptive and inferential statistics, specifically the independent sample t-test. Research data were obtained by administering pre-tests and post-tests on the water cycle topic. The data were analyzed using SPSS version 24. Based on the inferential statistical analysis, a post-test value of 0.000 < 0.05 was obtained. It can be concluded that the implementation of the STAD-type cooperative learning model has an effect on the science learning outcomes of Grade V students at SDN Panaikang 1, Panakukang District, Makassar City.